Inhibitory effects of antiviral compounds on respiratory syncytial virus replication in vitro. - Kawana, F (1987)
We examined the inhibitory effect of 20 antiviral compounds, including ribavirin, on the replication of respiratory syncytial virus in HeLa and HEp-2 cell cultures. Of the compounds studied, pyrazofurin and 3-deazaguanine emerged as more potent inhibitors of respiratory syncytial virus than ribavirin. Based on their inhibitory effect on the cytopathogenicity of respiratory syncytial virus in HeLa cells, the average 50% effective dose of pyrazofurin and 3-deazaguanine for eight strains was 0.07 and 1.65 micrograms/ml, respectively; that of ribavirin was 5.82 micrograms/ml. The cytotoxicity of these compounds for HeLa cells was examined by monitoring the incorporation of radiolabeled uridine into cellular RNA. The selectivity indexes of pyrazofurin and 3-deazaguanine exceeded that of ribavirin by 70- and 11-fold, respectively. Pyrazofurin, 3-deazaguanine, and ribavirin inhibited both viral antigen expression and syncytium formation in HeLa cell cultures, as assessed by an indirect immunofluorescence assay. In these assays, pyrazofurin and 3-deazaguanine again proved more potent than ribavirin. 2,5-Diamidinoindole and carbodine were less potent than ribavirin. Various other compounds, i.e., 3-adenin-9-yl-2-hydroxypropanoic acid isobutyl ester, 3-deazauridine, 3'-C-methyluridine, 5'-deoxy-5-fluorouridine, 5-cyanoimidazole-4-carboxamide, and its ribofuranosyl derivative, did not inhibit the cytopathic effect of the Long strain of respiratory syncytial virus at concentrations greater than or equal to 125 micrograms/ml. Tubercidin, 5-chlorotubercidin, xylotubercidin, neplanocin A, thiosemicarbazone R, and 3-methylquercetine were too toxic to HeLa cells for their inhibitory effects on respiratory syncytial virus to be examined.